Durabilitas Campuran AC-BC Yang Menggunakan Agregat Limbah Beton - Arnol Mambela; Rais Rachman; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This study aims to determine the value of stability, flow and the effect of immersion time on the durability of the AC-BC mixture by using time variations by utilizing Concrete Waste aggregate based on laboratory testing. The method used in this study is the Marshall method to determine the strength of the mixture after immersion. From the results of research conducted through the marshall immersion test with immersion duration of 0.50 hours, 12 hours, 24 hours, 36 hours, 48 ​​hours, and 60 hours. The results of the marshall immersion test showed that the stability value was between 1053.36 Kg - 1304.73 Kg, the flow was between 2.58 mm - 3.00 mm, and the immersion duration was obtained which affected the durability where the longer the immersion duration the smaller the stability value and the lower the stability value. flow is getting bigger.